Development of SuperSmart Grids for a more efficient utilisation of electricity from renewable sources - Battaglini, Antonella; Lilliestam, Johan; Haas, Armin; Patt, Anthony (Journal of Cleaner Production, 2009)
If Europe is serious about reaching its target to keep global mean temperature increase below 2 °C, it must strive for a 100% renewable electricity system by 2050. The SuperSmart Grid approach combines what is often perceived as two exclusive alternatives: wide area power generation and decentralised power generation. We argue that by combining these, in fact, complementary measures, it is possible to address the crucial issue of renewable generation-fluctuating supply-in a comprehensive as well as in a technologically and economically viable manner. Thus, the SuperSmart Grid simultaneously can contribute to energy security, climate security, social security, and national security. © 2009 Elsevier Ltd. All rights reserved.
CRIS-Team Scopus Importer:2023-06-14
Keywords: Climate change; Electricity networks; Global warming; Renewable electricity; Smartgrid; Supergrid; SuperSmart Grid